Buying Practices and Prevalence of Adulteration in Selected Food items in a Rural Area of Wardha District: A Cross - Sectional Study - Khapre MP; Mudey A; Sonali Chaudhary; Wagh V; Ajay Dawale (Online Journal of Health & Allied Sciences, 2011)
Introduction: Food adulteration in India includes both willful adulteration and substandard food which do not confirm to prescribe food standard. There is striking paucity of reliable data with regard to extent of adulteration and documentation of food borne illnesses reflecting lack of attention and focus on this problem. Objectives: To find the prevalence of food adulteration, buying practices of selected food items and their awareness towards food adulteration act. Also assess relationship between per-capita incomes, education of respondents, and food borne illnesses with magnitude of adulteration in each house-hold. Methods: With the best estimate of 50%, sample size comes to 89. By stratifying the village according to social strata and randomly selecting the households with PPS. Questionnaire was administered to fulfill our objectives and food items were tested. Data analyzed by numeral with percentage, Pearson moment correlation, F test and chi square test. Results: In 68.5% Households, wife (home-maker) buys the grocery. Majority of them never read the food labels. All the selected food items were adulterated ranging from 76 % to 11%. Mean percentage of purity was highest in literates (47.5 ± 22.48) than illiterates and just literates. Food borne illness was prevalent in households with low purity of food. Association was found between per capita income and percentage of purity (0.765).